Systemic adverse events after intravitreal bevacizumab versus ranibizumab for age-related macular degeneration: a meta-analysis. - Wei Wang (Public Library of Science (PLoS), 2014)
Objective To assess whether the incidence of systemic adverse events differs between those who used bevacizumab and those who used ranibizumab in the treatment of age-related macular degeneration (AMD). Methods A systematic literature search was conducted to identify randomised controlled trials (RCTs) comparing the use of intravitreal bevacizumab with the use of ranibizumab in AMD patients. Results were expressed as risk ratios (RRs) with accompanying 95% confidence intervals (CIs). The data were pooled using the fixed-effect or random-effect model according to the heterogeneity present. Results Four RCTs were included in the final meta-analysis. Overall, the quality of the evidence was high. There were 2,613 treated patients: 1,291 treated with bevacizumab and 1,322 treated with ranibicizumab. No significant differences between bevacizumab use and ranizumab use were found in terms of the incidence of death from all causes, arteriothrombotic events, stroke, nonfatal myocardial infarction, vascular death, venous thrombotic events, and hypertension, with the pooled RRs being 1.11 (0.77, 1.61), 1.03 (0.69,1.55), 0.84 (0.39,1.80), 0.97 (0.48, 1.96), 1.24 (0.63, 2.44), 2.38 (0.94, 6.04), and 1.02 (0.29, 3.62), respectively. Conclusions The meta-analysis shows that both treatments are comparably safe. However, the findings from our study must be confirmed in future research via well-designed cohort or intervention studies because of the limited number of studies.